A Combined Services Area Project: Strategies for a Successful Operation. Issue 3 (3rd July 2017) - Wang, Bing; Henson, Bruce
ABSTRACT: Since 2011, Georgia Tech Library has been undergoing a series of changes to redefine the 21st century research library. At the beginning of these changes were combining reference, circulation, and technology support into a one-stop-shop service model. Although operations under the integrated services model faced many challenges, forming a new department to include all staff members who provide such integrated services and helping these employees develop and maintain their competency are two key successful factors.